The Effectiveness of Video Scribe Sparkol on EFL Students’ Grammar Ability - Viola Putri Syafii; Ahmad Ridho Rojabi (Tell : Teaching of English Language and Literature Journal, 2021)
Grammar is one of the most important aspects as it integrates with four language skills, and it enhances the learners’ fluency. However, some students still get difficulty in understanding the grammar patterns and difficulty in composing grammatical sentences. One of the methods that can be implemented in teaching grammar is Video Scribe Sparkol. This study intends to determine whether or not the employment of Video Scribe Sparkol influences students' grammatical skills. This quantitative-experimental research involved the investigation of two classes; experimental and control.  The experimental class was given treatment by using Video Scribe Sparkol, while the control class was taught conventionally (without using any media). The experimental class's SPSS data indicated that a  pre-test average score was 68.15,  and the post-test average score was 83.23. It indicated a  highly significant improvement in the experimental class's score. Meanwhile,  the average score of the control class's pre-test was  70.96,  and their post-test average score was 78.09. As the significance sig. (2 tailed) of the Independent Sample t-test was  0.027 < 0.05, which means that the null hypothesis (H0) is rejected. Thus, there is a significant difference between the average score of the experimental and the control class. The results revealed that Video Scribe has a significant impact on learners’ grammar ability, and it can motivate and engage them in grammar activities due to interesting images, animations, and audiovisuals on its features. Thus, further researchers need to investigate the students’ motivation toward this method.